2018
DOI: 10.1186/s12885-018-4347-0
|View full text |Cite
|
Sign up to set email alerts
|

Active DNA end processing in micronuclei of ovarian cancer cells

Abstract: BackgroundOvarian cancer is one of the most deadly gynecological malignancies and inclined to recurrence and drug resistance. Previous studies showed that the tumorigenesis of ovarian cancers and their major histotypes are associated with genomic instability caused by defined sets of pathogenic mutations. In contrast, the mechanism that influences the development of drug resistance and disease recurrence is not well elucidated. Solid tumors are prone to chromosomal instability (CIN) and micronuclei formation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…1F) were also positive for γH2AX foci. Since several DNA damage sensing, repair and signaling factors, including ATM, MDC1, NBS1 (component of MRN complex), BRCA1, P53 and RPA32, are shown to localized in the micronuclei, 35,36 it is reasonable to speculate that one of these factors may modulate the recruitment of cGAS to micronuclei in response to DNA damage. Initially, we examined the localization of MDC1, ATM, MRE11, and NBS1 to the micronuclei and found that ~18-40% of micronuclei were positive for MDC1, phosphorylated ATM (S1981), MRE11 and NBS1 in response to 6-thio-dG ( Figs.…”
Section: Results Cgas Is Recruited To Only a Sub-set Of Micronucleimentioning
confidence: 99%
“…1F) were also positive for γH2AX foci. Since several DNA damage sensing, repair and signaling factors, including ATM, MDC1, NBS1 (component of MRN complex), BRCA1, P53 and RPA32, are shown to localized in the micronuclei, 35,36 it is reasonable to speculate that one of these factors may modulate the recruitment of cGAS to micronuclei in response to DNA damage. Initially, we examined the localization of MDC1, ATM, MRE11, and NBS1 to the micronuclei and found that ~18-40% of micronuclei were positive for MDC1, phosphorylated ATM (S1981), MRE11 and NBS1 in response to 6-thio-dG ( Figs.…”
Section: Results Cgas Is Recruited To Only a Sub-set Of Micronucleimentioning
confidence: 99%
“…Micronuclei generated from laggards are less condensed than those generated from chromatin bridges 37 . Some micronuclei undergo active DNA end processing to generate single‐strand DNA (ssDNA) 44 …”
Section: Not All Micronuclei Are Equal: Heterogeneities In the Sourcementioning
confidence: 99%
“…Similarly, lamin‐B positive DMs‐derived micronuclei are as actively transcribed as main nuclei 46 . Spontaneous‐occurring and ionizing radiation‐induced micronuclei exhibit opposite capacity to recruit DNA damage binding proteins γH2AX and 53BP1, 44 indicating that micronuclei of different origins display heterogeneity in DDR signaling. Similarly, the γH2AX and 53BP1 binding capacity is also different between ssDNA‐enriched and ssDNA‐absent micronuclei, 44 suggesting chromatin structure also impact DDR signaling in micronuclei.…”
Section: Not All Micronuclei Are Equal: Heterogeneities In the Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, many genotoxic studies have sought to determine the impact compounds have on genome stability by manually assessing the presence of micronuclei following a treatment [4,5], while more recent studies have employed micronucleus formation assays to uncover genes with pathogenic implications in cancer [6][7][8]. In this regard, numerous cytological studies have identified micronuclei within various cancer contexts including head and neck, ovarian, and breast cancers [9][10][11]. Interestingly, the presence of micronuclei in precursor lesions is associated with an increased risk of developing certain cancers [12][13][14][15], suggesting that the presence and frequency of micronuclei may hold clinical value as diagnostic and prognostic biomarkers.…”
Section: Introductionmentioning
confidence: 99%